2003
DOI: 10.1177/014556130308200717
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cell Sarcoma of the Tonsil: Report of a Rare Case

Abstract: Follicular dendriti c cell tumors are extremely rare. Only 17 cases have been previously described in the literature, and only three ofthem involved prima ry tumors ofthe oral cavity. We describe a new case of the latter, which occurred in a 51-year-old man who sought evaluationfo r a painl ess enlargement of his lef t palatine tonsil. The tonsil was excised, and histologic examination revealed that the tumor was a prima ry sarcoma that had arisen fr om the dendritic reticulum cells of the palatin e tonsil. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…In cases in which metastasis to regional lymph nodes is suspected on imaging studies, a neck dissection is recommended 3. In the current case, a neck dissection was not performed because no findings suggestive of metastasis to the neck lymph nodes were observed on imaging studies following the diagnostic tonsillectomy.…”
Section: Discussionmentioning
confidence: 94%
“…In cases in which metastasis to regional lymph nodes is suspected on imaging studies, a neck dissection is recommended 3. In the current case, a neck dissection was not performed because no findings suggestive of metastasis to the neck lymph nodes were observed on imaging studies following the diagnostic tonsillectomy.…”
Section: Discussionmentioning
confidence: 94%
“…Chan et al [2] consider systemic radiotherapy as the treatment of choice, while other authors such as Perez-Ordonez and Rosai [10,13] prefer this therapy as an option for the treatment of lymph node metastasis of the neck region, positive margins or recurrence of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Then, in 1986, Monda et al reported the first case of primary neoplasm of FDCs in the lymph node [9]. To date, only a few cases of FDC sarcoma in the tonsil have been described [13]. Few extra nodal FDCS were reported by Youens and Waugh [14], and in the pharyngeal or abdominal region [12].…”
Section: General Information On the Diseasementioning
confidence: 99%
“…La extirpación quirúrgica completa es el tratamiento de referencia del FDCS de amígdala 2,6,8,9 ; algunos autores abogan por la disección de cuello en el caso de evidencia de metástasis ganglionar 3 . Se desconoce el beneficio de la radiación o quimioterapia posquirúrgicas para la supervivencia 7 .…”
Section: Discussionunclassified